Nem localistas nem setorialistas, as assembleias estaduais são “classe-médistas”: ganhos e perdas das leis estaduais durante a crise da covid-19 - JUNQUEIRA, Murilo de Oliveira (Câmara dos deputados, 2021)
This aim of this paper is to analyze the content of the state’s laws in the fight against the economic and social crisis generated by Covid-19. Sixteen Brazilian states were analyzed, including 309 laws. The methodology used was content analysis and exploratory data analysis. It was observed that the pattern of relations between the Legislative Assembly and State governments varied enormously, with some parliaments passing many laws and others very few. Especially in the parliaments that passed many laws, there was a notable increase in economic interventionism, mainly in policies that benefited, in a diffuse way, the middle class. This finding is contrary to what is expected by the literature, which advocates that the greatest interest of parliamentarians are measures of local or sectorial interest.